The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2022
DOI: 10.4081/pmc.2022.280
|View full text |Cite
|
Sign up to set email alerts
|

Achilles tendon surgery in clubfoot: Are long term sequelae predictable?

Abstract: Congenital Clubfoot (CCF) treatment involves a surgical procedure on the Achilles tendon most of the time, i.e. tenotomy or, in selected cases, Z-plasty lengthening. Many authors have studied the outcomes of Achilles tenotomy, describing complete clinical and ultrasound tendon fibers integrity restoration 3-6 weeks after surgery. Nevertheless, little is known about the mechanical properties of the operated tendon. Recently, cases of subcutaneous rupture of the Achilles tendon have been described in adolescents… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…2 Achilles intratendinous ossification is the only long-term complication described in the literature after undergoing Achilles tenotomy for congenital talipes equinovarus. 3 However, the posttenotomy tendon morphology with its striation pattern might be more prone to develop tendinopathy as well, according to the case reported in this article. This type of Achilles tendinopathy seems to respond well to standard tendinopathy treatments.…”
mentioning
confidence: 61%
See 1 more Smart Citation
“…2 Achilles intratendinous ossification is the only long-term complication described in the literature after undergoing Achilles tenotomy for congenital talipes equinovarus. 3 However, the posttenotomy tendon morphology with its striation pattern might be more prone to develop tendinopathy as well, according to the case reported in this article. This type of Achilles tendinopathy seems to respond well to standard tendinopathy treatments.…”
mentioning
confidence: 61%
“…As a result, weight-bearing tolerance, mobility, and pain are generally improved 2 . Achilles intratendinous ossification is the only long-term complication described in the literature after undergoing Achilles tenotomy for congenital talipes equinovarus 3 . However, the posttenotomy tendon morphology with its striation pattern might be more prone to develop tendinopathy as well, according to the case reported in this article.…”
mentioning
confidence: 64%
“…In both cases, intraoperative findings included a significant amount of scar tissue at the distal end of the tendon. Moreover, Pedrotti et al 17 and Manfreda et al 18 reported calcification and rupture of the Achilles tendon in adults with a history of treatment for clubfoot. Although these cases differed from the present case in that they had previously undergone more invasive surgery, we believe that the pathophysiology of calcification and rupture because of degeneration of the Achilles tendon is similar to that of the present case.…”
Section: Discussionmentioning
confidence: 99%